2022
DOI: 10.1021/acssuschemeng.2c03324
|View full text |Cite
|
Sign up to set email alerts
|

One-Step Hydrothermal Synthesis of Nitrogen-Doped Carbonized Polymer Dots with Full-Band Absorption for Skin Protection

Abstract: Long-term and excessive ultraviolet (UV) radiation will trigger various skin diseases, and traditional organic and inorganic sunscreens possess disadvantages such as biocompatibility and being prone to aggregation. Carbon polymer dots (CPDs) are an excellent candidate for UV absorbers due to their polyfunctional groups, superior stabilization, and low cytotoxicity. In this study, we explored the conformational relationship of the structure of CPDs on the full-band absorbers by synthesizing various CPDs using a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 54 publications
1
12
0
Order By: Relevance
“…UV-vis absorption is an important parameter for numerous applications and products, such as sunscreens and makeups. It is apparent that G-CDs exhibited a strong absorption band centered at 262 nm (Figure 4a), which is attributed to the aromatic π-π* transitions from C=C and n-π* transition of C=O bond, [28] consistent with the FT-IR and XPS results. Despite having lower UV-vis absorption than G-CDs, U-CDs, C-CDs, and T-CDs still possessed a strong UV-vis absorption.…”
Section: Optical Characterization Of Cdssupporting
confidence: 84%
See 2 more Smart Citations
“…UV-vis absorption is an important parameter for numerous applications and products, such as sunscreens and makeups. It is apparent that G-CDs exhibited a strong absorption band centered at 262 nm (Figure 4a), which is attributed to the aromatic π-π* transitions from C=C and n-π* transition of C=O bond, [28] consistent with the FT-IR and XPS results. Despite having lower UV-vis absorption than G-CDs, U-CDs, C-CDs, and T-CDs still possessed a strong UV-vis absorption.…”
Section: Optical Characterization Of Cdssupporting
confidence: 84%
“…[55][56][57] Furthermore, the longterm effects of sunscreen use may result in the increased production of free radicals, which can attack normal cells and contribute to oxidative stress, leading to several diseases and skin aging. [28,57] CDs are novel carbon nanomaterials with widely praiseworthy properties, especially their strong UV absorption and UV protection. [28] As shown in the UV-vis spectra above, all CDs demonstrated excellent UV absorption.…”
Section: Uv Protectionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the expensive price, lack of eco-friendliness, and incompatibility with hydrogel matrix of fluorescent monomers limit the further development of fluorescent smart hydrogels in this field. , Recently, carbon dots (CDs) has been widely known as a promising luminescent nanomaterial with abundant low-cost sources, facile synthetic methods, excellent biocompatibility, high chemical stability, significant water solubility, low cytotoxicity, and excellent optoelectronic properties, attracting great attention in many fields including biomedicine, catalysis, optoelectronic devices, and especially anticounterfeiting. Many scholars demonstrated that integrating CDs into desirable polymer matrix is a cost-effective and environmentally friendly method to develop flexible materials for information encryption. For instance, Xiong et al reported a flexible right-hand chiral fluorescent film with potential applications in sensing and anti-counterfeiting .…”
Section: Introductionmentioning
confidence: 99%
“…Among these properties, the absorption of UV for CDs is a newly developed process in recent years. Our research group has also carried out many studies on the UV absorption properties of CDs and applied them in the fields of UV shielding, sunscreen, healthy light source lamps, and so on. Hu et al synthesized full-band UV-absorbent water-soluble (NH,OH)-functionalized silicon quantum dots, investigated its stability, and compared their stability and UV absorptivity with commercial water-soluble UV absorbents .…”
Section: Introductionmentioning
confidence: 99%